2018
DOI: 10.1002/prp2.391
|View full text |Cite
|
Sign up to set email alerts
|

Electrical dynamics of isolated cerebral and skeletal muscle endothelial tubes: Differential roles of G‐protein‐coupled receptors and K+ channels

Abstract: Electrical dynamics of freshly isolated cerebral endothelium have not been determined independently of perivascular nerves and smooth muscle. We tested the hypothesis that endothelium of cerebral and skeletal muscle arteries differentially utilizes purinergic and muscarinic signaling pathways to activate endothelium‐derived hyperpolarization. Changes in membrane potential (V m) were recorded in intact endothelial tubes freshly isolated from posterior cerebral and superior epigastric arteries of male and female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 59 publications
4
16
0
Order By: Relevance
“…The V m must be as high as −90 mV at physiological temperature (37 °C) in order to bring transmembrane K + flux to equilibrium (E K ). For reference, vascular endothelial cells typically have a V m of ~−30 to −40 mV during rest, and activation of SK Ca /IK Ca channels alone using NS309 can increase V m to E K [37,41]. As a dominant form of K + channel expressed in the endothelial membrane, the SK Ca /IK Ca channels are tetrameric (four subunits), voltage-independent (from V m ~−80 to +10 mV [37]), and are constitutively bound to calmodulin binding sites for [Ca 2+ ] i [42].…”
Section: Significance Of Skca/ikca and Trp Channels In The Blood Vmentioning
confidence: 99%
“…The V m must be as high as −90 mV at physiological temperature (37 °C) in order to bring transmembrane K + flux to equilibrium (E K ). For reference, vascular endothelial cells typically have a V m of ~−30 to −40 mV during rest, and activation of SK Ca /IK Ca channels alone using NS309 can increase V m to E K [37,41]. As a dominant form of K + channel expressed in the endothelial membrane, the SK Ca /IK Ca channels are tetrameric (four subunits), voltage-independent (from V m ~−80 to +10 mV [37]), and are constitutively bound to calmodulin binding sites for [Ca 2+ ] i [42].…”
Section: Significance Of Skca/ikca and Trp Channels In The Blood Vmentioning
confidence: 99%
“…In addition to cellular/tissue damage caused by accumulated protein/DNA damage, molecular aging ‘programs’ (i.e., coherent and repeated pathological patterns of protein expression leading to stress-related damage) can also generate age-related increases in cellular senescence. Cell growth arrest and hyporesponsiveness to extrinsic stimuli via cell surface receptors, such as GPCRs, are hallmarks of senescent cells [ 122 , 123 , 124 , 125 ]. Cell senescence describes the process in which cells cease dividing, but do not enter an apoptotic state.…”
Section: G Protein-coupled Receptor Systems: Intersections With Dnmentioning
confidence: 99%
“…In particular, during endothelium-derived hyperpolarization (commonly known as EDH), intracellular Ca 2+ ([Ca 2+ ] i ) and electrical signaling in endothelial cells coordinate vasodilation among endothelial cells and their surrounding smooth muscle cells through gap junctions for arterial relaxation 4 . Physiological initiation of EDH sequentially entails stimulation of G q -coupled receptors (GPCRs), an increase in [Ca 2+ ] i , and activation of endothelial small- and intermediate-Ca 2+ -activated K + (SK Ca /IK Ca ) channels to hyperpolarize cerebral endothelial membrane potential (V m ) 5,6,7 . Thus, the intimate relationship of endothelial [Ca 2+ ] i and V m is integral to blood flow regulation and indispensable to cardio- and cerebrovascular function 6,8 .…”
Section: Introductionmentioning
confidence: 99%
“…Physiological initiation of EDH sequentially entails stimulation of G q -coupled receptors (GPCRs), an increase in [Ca 2+ ] i , and activation of endothelial small- and intermediate-Ca 2+ -activated K + (SK Ca /IK Ca ) channels to hyperpolarize cerebral endothelial membrane potential (V m ) 5,6,7 . Thus, the intimate relationship of endothelial [Ca 2+ ] i and V m is integral to blood flow regulation and indispensable to cardio- and cerebrovascular function 6,8 . Throughout the broader literature, numerous studies have reported the association of vascular endothelial dysfunction with the development of chronic diseases (e.g., hypertension, diabetes, heart failure, coronary artery disease, chronic renal failure, peripheral artery disease) 9,10 , indicating the significance of studying endothelial function in physiological as well as pathological conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation